2017
DOI: 10.1590/0104-6632.20170341s20150681
|View full text |Cite
|
Sign up to set email alerts
|

The Formation Behavior of a Single Bubble in Power-Law Fluids

Abstract: The formation behavior of a single bubble in power-law fluids (carboxymethyl cellulose solution, CMC) and Newtonian fluids (glycerol solution) was experimentally investigated via a high-speed camera. The effects of liquid property, orifice diameter and gas flow rate on bubble volume and aspect ratio were observed. It was found that the formation time and detaching volume increased with the increase of fluid viscosity. The increase of bubble aspect ratio during the bubble formation process was complex, with mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…It is found that these results are consistent as shown in figures 13 and 14. Furthermore, the evaluations of the present model are more accurate and have a good agreement with the previous studies as in [16,19,24,29,30]. We noticed that the time of growth and collapse plays a significant role in the problem, such that the growth time of the bubble is much greater than the collapse time as a result of the sudden collapse of the bubble that restricts the increase in pressure potential.…”
Section: Validation Of the Model And Comparative Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…It is found that these results are consistent as shown in figures 13 and 14. Furthermore, the evaluations of the present model are more accurate and have a good agreement with the previous studies as in [16,19,24,29,30]. We noticed that the time of growth and collapse plays a significant role in the problem, such that the growth time of the bubble is much greater than the collapse time as a result of the sudden collapse of the bubble that restricts the increase in pressure potential.…”
Section: Validation Of the Model And Comparative Analysissupporting
confidence: 86%
“…Subsequently, numerical, and experimental studies were implemented on the formation of bubbles in power-law fluids [22,25]. The behavior of a single vapor bubble in carboxymethyl cellulose (CMC) and glycerol solution is investigated experimentally by Li et al [30]. The growth of a vapor bubble in a superheated liquid was studied by many authors as in [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…There is a counteracting effect between the surface tension force and the resistance of ambient liquid. Moreover, the adhesion of the bubble to the inner wall of the nozzle is strengthened with the increase of the nozzle outlet diameter 23 . For mineral oil, the variation in nozzle outlet diameter leads to a more drastic change in the bubble detachment frequency.…”
Section: Resultsmentioning
confidence: 58%
“…International Journal of Chemical Engineering Furthermore, some scholars used the aspect ratio (E), defined as the ratio of the vertical diameter to the horizontal diameter, i.e., E � D Y /D X, to describe the bubble shapes [41][42][43][44]. Unfortunately, most mathematical models of eccentricity (e) and aspect ratio (E) are for Newtonian fluids and viscous non-Newtonian fluids, and limited studies have been conducted on viscoelastic fluids.…”
mentioning
confidence: 99%